2005
DOI: 10.1038/nm1332
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 signaling through the IL-13α2 receptor is involved in induction of TGF-β1 production and fibrosis

Abstract: Interleukin (IL)-13 is a major inducer of fibrosis in many chronic infectious and autoimmune diseases. In studies of the mechanisms underlying such induction, we found that IL-13 induces transforming growth factor (TGF)-beta(1) in macrophages through a two-stage process involving, first, the induction of a receptor formerly considered to function only as a decoy receptor, IL-13Ralpha(2). Such induction requires IL-13 (or IL-4) and tumor necrosis factor (TNF)-alpha. Second, it involves IL-13 signaling through I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
687
5
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 801 publications
(734 citation statements)
references
References 43 publications
24
687
5
12
Order By: Relevance
“…IL-13Rα2 is a membrane glycoprotein that mediates activation of the TGF-β1 promoter upon stimulation by IL-13 (or IL-4) and tumor necrosis factor (TNF)-α [34]. IL-13Rα2 has attracted significant attention as a target for glioma therapy [35] because this receptor is overexpressed by more than 80% of adult malignant gliomas but is not expressed at detectable levels in normal brain tissues or at high levels in other normal organs except the testis [36].…”
Section: Discussionmentioning
confidence: 99%
“…IL-13Rα2 is a membrane glycoprotein that mediates activation of the TGF-β1 promoter upon stimulation by IL-13 (or IL-4) and tumor necrosis factor (TNF)-α [34]. IL-13Rα2 has attracted significant attention as a target for glioma therapy [35] because this receptor is overexpressed by more than 80% of adult malignant gliomas but is not expressed at detectable levels in normal brain tissues or at high levels in other normal organs except the testis [36].…”
Section: Discussionmentioning
confidence: 99%
“…By monitoring the development of lung inflammation in IL-13 transgenic mice, Lanone and colleagues [59] demonstrated that IL-13 can induce alveolar remodeling, respiratory failure and death, and that upregulation of MMP-2, -9, -13 and -14 by IL-13 is mediated at least partially by a MMP-12-dependent pathway. Other studies also suggested that IL-13 was able to induce transforming growth factor-β1 (TGF-β1) expression in macrophages through the activation of a specific AP-1 complex variant in bleomycininduced lung fibrosis [60]. TGF-β1, that is often considered as an anti-inflammatory growth factor, inhibits cytokine-mediated induction of MMP-12 mRNA as well as protein and enzymatic activity in chondrosarcoma-derived HTB-94 cells [37].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…On the other hand, IL13Ra2 does not seem to require IL-4Ra and by itself binds IL-13 with high affinity, internalizes and also mediates signal transduction. [8][9][10][11] To determine the significance of IL-13Ra2 expression', we have discovered that over-expression of IL13Ra2 increases cancer invasion and metastasis and shortens survival time of mice with human pancreatic cancer. 12 Whether this novel function of IL-13Ra2 is extendable to other human cancers is not known.…”
mentioning
confidence: 99%